2014
DOI: 10.1155/2014/859879
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Degradation of Masonry Mortar in Historic Brick Structures

Abstract: This study characterized mortars from a masonry fortification in Charleston, South Carolina (USA), harbor where construction was during the period 1839-1860. This location for analysis was interesting because of the sea water impingement on the structure. The study was included as part of an overall structural assessment with restoration as an objective. The mortars were found to be cement, lime, and sand mixtures in proportions similar to ones expected from the historic literature, that is, one part binder to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The chemical analysis was carried out using a method that analyzes the filtrate containing oxides of elements present in a sample [20] ; from that, the cementation index (CI) was calculated. The cementation of historic mortars is one of the essential aspects to investigate during the characterization process [22] . The procedure identifies the element oxides such as silica (Si), aluminium (Al), iron (Fe) and magnesium (Mg) to be used for calculation of CI as shown in Equation ( 1) [22] .…”
Section: Methods For Materials Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical analysis was carried out using a method that analyzes the filtrate containing oxides of elements present in a sample [20] ; from that, the cementation index (CI) was calculated. The cementation of historic mortars is one of the essential aspects to investigate during the characterization process [22] . The procedure identifies the element oxides such as silica (Si), aluminium (Al), iron (Fe) and magnesium (Mg) to be used for calculation of CI as shown in Equation ( 1) [22] .…”
Section: Methods For Materials Analysesmentioning
confidence: 99%
“…The cementation of historic mortars is one of the essential aspects to investigate during the characterization process [22] . The procedure identifies the element oxides such as silica (Si), aluminium (Al), iron (Fe) and magnesium (Mg) to be used for calculation of CI as shown in Equation ( 1) [22] .…”
Section: Methods For Materials Analysesmentioning
confidence: 99%
“…Structural evaluation of buildings [29] and stone conservation techniques and strategies [30][31][32] require an interdisciplinary approach based on scientific assessment. Preservation of such buildings requires the availability of knowledge in building techniques, precise documentation of dimensions and elevations, structural stability analysis, and materials characterization [33]. It is also required for their conservation assessment for safe use guidelines.…”
Section: Ghulammentioning
confidence: 99%
“…Where: SiO 2 = silicon oxide Al 2 O 3 = aluminium oxide Fe 2 O 3 = iron oxide CaO = calcium oxide MgO = magnesium oxide According to Martínez et al (2013) and Brosnan (2014), the CI quantities as identified in Table 1 are an indication of lime and cement content in mortar samples.…”
Section: Chemical Characterisationmentioning
confidence: 99%